Impact of Nutrient Availability on Tertiary Wastewater Treatment by Chlorella vulgaris: Chamberlin et al. (1st November 2018) - Chamberlin, John; Harrison, Kristen; Zhang, Wen
ABSTRACT: : Algae can use excessive nutrients from wastewater effluent to generate beneficial products such as biofuels. However, fluctuation of wastewater characteristics could hinder the implementation of tertiary algal treatment. This study aims to identify the impact of nutrient availability on Chlorella vulgaris 's ability to remove nitrogen and phosphorus from wastewater, and its potential as a biofuel feedstock. Experiments using synthetic wastewater with varying concentrations of nitrate and phosphate showed C. vulgaris continued to remove either nutrient when the other was exhausted. Nitrogen starvation led the algae to accumulate the highest amount of neutral lipid; however, the exhaustion of phosphorus did not produce such impact. Synergistic effect was also observed between C. vulgaris and indigenous microorganisms in nutrient removal from real wastewater effluent. The results showed C. vulgaris can survive in a range of nutrient‐limiting conditions, making tertiary algal treatment applicable following various secondary treatment regimes.